1997
DOI: 10.1002/(sici)1099-1379(199705)18:3<275::aid-job796>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Collectivistic orientation in teams: an individual and group-level analysis

Abstract: SummaryWith the increasing use of work teams in U.S. industry, understanding team members' collectivistic orientation toward group goals and activities is critical for developing cooperative and productive teams. Using the research on expectancy theory, selfecacy, locus of control, and individualism±collectivism, collectivism is examined as both an individual dierence variable and a group composition variable. One hundred and forty-eight individuals (comprising 33 groups) working on a complex and interdependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
302
0
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 352 publications
(329 citation statements)
references
References 60 publications
6
302
0
13
Order By: Relevance
“…Oetzel (1998) found that individualistic European-American groups had a greater number of conflicts, fewer cooperating tactics, and more competing tactics than collectivistic Japanese-American groups. In two studies also discussed in the individual level section, Pillai and Meindl (1998) found that COL was positively related to charismatic leadership emergence in a field study of 101 work groups; and Eby and Dobbins (1997) found that team collectivistic orientation was positively related to team cooperation, and team cooperation mediated the relationship between team collectivistic orientation and team performance in a study of 33 student teams. Kirkman and Shapiro (2001b) found that COL was negatively related to the level of team member resistance to the team-related aspects of SMWTs, and that resistance mediated the relationships COL had with team cooperation, empowerment, and productivity.…”
Section: Research Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…Oetzel (1998) found that individualistic European-American groups had a greater number of conflicts, fewer cooperating tactics, and more competing tactics than collectivistic Japanese-American groups. In two studies also discussed in the individual level section, Pillai and Meindl (1998) found that COL was positively related to charismatic leadership emergence in a field study of 101 work groups; and Eby and Dobbins (1997) found that team collectivistic orientation was positively related to team cooperation, and team cooperation mediated the relationship between team collectivistic orientation and team performance in a study of 33 student teams. Kirkman and Shapiro (2001b) found that COL was negatively related to the level of team member resistance to the team-related aspects of SMWTs, and that resistance mediated the relationships COL had with team cooperation, empowerment, and productivity.…”
Section: Research Challengesmentioning
confidence: 99%
“…Cultural distance on COL (i.e., how different, on average, each individual is from other group members) was negatively related to group receptiveness. In a sample of US undergraduates, COL was positively related to selfefficacy for teamwork, need for social approval, and positive past experience working in teams (Eby and Dobbins, 1997). In support of their theoretical model (Kirkman and Shapiro, 1997), found that COL was positively related to receptivity to team-based rewards using employee surveys in a US insurance company.…”
Section: Reward Allocation (8)mentioning
confidence: 99%
See 2 more Smart Citations
“…The average estimates of IRR were 0.912 for relational benefit, 0.901 for relational risk, and 0.912 for information sharing, respectively. All estimates exceeded the recommended cut-off value of 0.7 [50], indicating the response consistency between the two groups.…”
Section: Data Collectionmentioning
confidence: 99%